Analisis Komparatif Kinerja Bank Syariah Berdasarkan Metode Islamic Performance Index Dan RGEC Pada Bank Syariah Di Indonesia - Vandarina Ralda; Isfandayani Isfandayani (At-Tamwil: Journal of Islamic Economics and Finance, 2022)
This study aims to analyze the comparison of bank performance Sharia General based on Risk Profile, Good Corporate approach Governance (GCG), Earnings, Capital (RGEC) and Islamic Performance Index (IPI). The research period used is 2015-2019. This research using a quantitative approach. The research population covers the entire Bank General Sharia registered with the Financial Services Authority (OJK) for 2015-2019 period. The sample was determined by purposive sampling and obtained 10 Islamic Commercial Banks. This research uses descriptive analysis and using Cartesian RGEC and IPI Charts to determine the Bank's position Sharia General. The results of this study indicate that commercial banks Sharia is in a different quadratic. Bank Muamlat Indonesia, BNI Syariah and Bank Syariah Mandiri are in the Upper Left Quadrant (ULQ) which means the value of the Islamic Performance Index (IPI) is high but the value of The RGEC is low. Then, BRI Syariah in the Lower Left Quadrant (LLQ) which means that the RGEC and Islamic Performance Index (IPI) values ​​are low.Furthermore, Victoria Sharia Bank, Panin Dubai Sharia Bank, Sharia Bank Bukopin and BCA Syariah in the Upper Right Quadrant (URQ) which it means that the RGEC and Islamic Performance Index (IPI) values ​​are high. Whereas,Bank Jabar Banten (BJB) Syariah and Bank Mega Syariah in the Lower quadrant Right Quadran (LRQ) which means the RGEC value is high but Islamic His Performance Index (IPI) is low.